Use of (GIS)Techniques to Study a New City Site as a Solution for Urban Expansion in Lattakia Governorate - عباس اياد; شعبان فادي; الجبيلي كرم (Latakia University Journal -Engineering Sciences Series, 2020)
Regional planning is currently one of the pillars of the state and a measure of its development, because planning works to show the current or the future problems, and puts the appropriate solutions. So there is no doubt that the population is the main goal of any planning process by ensuring the various requirements of life for the increasing number of them year after year. Finding adequate housing is therefore one of the first steps in the planning process. The problem of population growth is one of the most prominent problems facing countries at present time. This is evident in city centers, which results in many problems such as informal housing. In this study, we had a spatial study to determine the best location for establishing a new city in order to accommodate the increasing number of population within the Lattakia Governorate (Syrian Arab Republic), and we also achieved a population study in order to determine the future population growth. Geographic information systems (GIS) have proven its efficiency in spatial and descriptive data management and analysis, so they have been relied upon to determine the appropriate places for urban expansion based on a set of criteria collected from a range of research that affect the selection process of these areas, through spatial analysis tools within the GIS software to reach the appropriate areas of expansion to accommodate the expected population growth.